COMPARISON OF ANGLE OPENING DISTANCE AND TRABECULAR IRIS SPACE AREA BEFORE AND AFTER LASER PERIPHERAL IRIDOTOMY IN ANGLE CLOSURE DISEASE: Oral Presentation - Observational Study - Resident - Ramdhani, Rizki Fasa; Rifada, R. Maula; Irfani, Irawati; Gustianty, Elsa; Umbara, Sonie (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesLaser peripheral iridotomy (LPI) is the standard first-line therapy in angle closure disease toincrease anterior chamber angle width. Spectral Domain Anterior Segment Optical CoherenceTomography (SD AS-OCT) is an instrument that has a quantitative parameter to measure anteriorchamber angle. Angle opening distance (AOD) and trabecular iris space area (TISA) are quantitativeparameters in SD AS-OCT. The purpose of this study is to compare AOD and TISA before and oneweek after LPI in angle closure disease. MethodsThis is an analytical prospective study with a cross-sectional study design. Twenty-two eyes withangle closure disease that met inclusion and exclusion criteria underwent LPI and SD AS-OCT beforeand one week after LPI. Analysis was performed using SD AS-OCT parameters, such as AOD(AOD500, AOD750) and TISA (TISA500, TISA750) in the temporal, nasal quadrants, and average. ResultsTwenty-two eyes with angle closure are divided into nine eyes with primary angle closure suspect,seven eyes with primary angle closure, and six eyes with primary angle closure glaucoma. The meanage of participants was 57.86±7.63 years. There was a significant increase in AOD500, AOD750,TISA500, and TISA750 in the temporal and nasal quadrants, as well as in the average (P=0.0001)based on a paired t test or Wilcoxon as an alternative. Average AOD750 had the highest T-value (T=6.329) with a mean 0.20±0.096 before LPI and 0.31±0.144 one week after LPI. ConclusionThere was a significant increase in AOD and TISA after one week LPI in angle closure disease.